Perencanaan Konten Media Sosial Dalam Event Road Tour Legacy Of Java X Sidji Batik Coffee Series - Siti Komsiah; Joachim David Magetanapuang; Cherly Kemala Ulfa; Dewi Maharani Rachmaningsih; Maulidia Eka Sitadewi; William Tristan (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The purpose of this research is to design social media content in order to promote the "Road Tour Legacy of Java Batik Sidji X Coffee Series" event. This design activity starts with qualitative data collection to find out the promotional media planning used. Data collection techniques were carried out by conducting interviews and direct observation of one of the artists involved in the event. The results showed that the design of event content was carried out by determining the platform, determining the content, SWOT analysis & evaluation (Strengths, Weaknesses, Opportunities, and Threats), and Action & Communication. about Batik on the Youtube Channel, and the information provided by Batik Sidji via Instagram can attract public attention to the art of Batik.